2017
DOI: 10.7759/cureus.1641
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Visual Outcomes and Patient Satisfaction Between Photorefractive Keratectomy and Femtosecond Laser-Assisted In Situ Keratomileusis

Abstract: PurposeTo compare visual outcomes and satisfaction among patients of photorefractive keratectomy (PRK; Wavelight EX 500, Alcon, Ft Worth, TX, USA) and femtosecond laser-assisted in situ keratomileusis (FAL; Wavelight FS 200 laser and Wavelight EX 500, Alcon, Ft Worth, TX, USA).MethodsWe performed a retrospective study of 409 eyes in 207 patients that underwent either PRK (n=90) or FAL (n=117) at the two centers of Hashmanis Hospital, Karachi, Pakistan. The included refractive outcomes were sphere diopters (D),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…In a local study from Pakistan, although superior visual outcomes were reported with LASIK but patients satisfaction rate was higher in simple PRK due to the higher cost of LASIK. 19 In T-PRK and LASIK, the difference in the cost is not very much. Hence, satisfaction level of the patient is related with the visual outcome as compared to the cost.…”
Section: Discussionmentioning
confidence: 99%
“…In a local study from Pakistan, although superior visual outcomes were reported with LASIK but patients satisfaction rate was higher in simple PRK due to the higher cost of LASIK. 19 In T-PRK and LASIK, the difference in the cost is not very much. Hence, satisfaction level of the patient is related with the visual outcome as compared to the cost.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mitomycin C on the stromal bed after ablation has allowed PRK surgeries in patients with high myopia by avoiding the appearance of haze in the postoperative period [ 8 , 9 , 17 ]. Less postoperative pain, fast visual recovery, and minimal incidence of haze has made FS-LASIK the preferred procedure in refractive surgery [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of FS-LASIK procedures has increased and surpasses the number of PRK procedures owing to faster visual recovery, less pain, and better ametropic range capability compared to following the former procedure [ 16 , 17 , 18 ]. PRK is still performed today, especially in corneas with superficial scarring, for epithelial dystrophies or recurrent erosions, in thin corneas, after penetrating keratoplasty, and for refractive retreatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study protocol [ 11 , 12 ] and reasons for exclusion [ 13 ] have been discussed in previous studies. Included in the study were patients aged 18 years or over who sought LASIK eye surgery for spectacle independence.…”
Section: Methodsmentioning
confidence: 99%